Attitudes toward global and national climate policies in Finland - The significance of climate change risk perception and urban/rural-domicile - Sivonen Jukka (Springer, 2025)
This paper examines public support for global- and national-level climate policy instruments in Finland, and the ways urban/rural-domicile and climate change risk perception predict people's attitudes toward climate policies. Moreover, this study analyzes the degree to which perception of closeness to the district modifies people's climate policy attitudes. The research method employed was ordinal logistic regression and data were from the demographically representative Finland 2019-survey (n = 1742 and response activity = 44%). According to the results, subsidizing renewable energy is an especially popular climate policy instrument, whereas approving new nuclear plants is rather unpopular. Policy instruments were typically more popular at the global level than they were at the national level. Perception of climate change risk was especially strongly linked with support for a national carbon tax. The effect of urban/rural-domicile and subjective closeness to the district on the attitudes was highly dependent on the policy instrument in question. The study contributes to the understanding of how climate policy attitudes vary depending on the climate change risk perception, urban/rural-domicile, and the instrument-type.